2016
DOI: 10.3892/ijmm.2016.2676
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin exerts antitumor effects in retinoblastoma cells by regulating the JNK and p38 MAPK pathways

Abstract: Curcumin, a naturally occurring polyphenolic compound present in turmeric (Curcuma longa), exerts antitumor effects in various types of malignancy. However, the precise mechanisms responsible for the effects of curcumin on retinoblastoma (RB) cells have not been fully explored. In the present study, the molecular mechanisms by which curcumin exerts its anticancer effects in RB Y79 cells were investigated. The results showed that curcumin reduced cell viability in Y79 cells. Curcumin induced G1 phase arrest thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 36 publications
(35 reference statements)
5
26
0
Order By: Relevance
“…Besides, based on the data in the current study we inferred that curcumin-suppressed Rb cells proliferation might be via modulation of cell cycle, as CyclinD1 was down-regulated and p21 was up-regulated by addition of curcumin. Similar finding was reported by Yu et al [ 31 ] that curcumin induced G1 phase arrest via down-regulations of Cyclin D3, CDK2/6, and up-regulations of p21 and p27. CyclinD1 and p21 are two key molecules in cell-cycle progression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, based on the data in the current study we inferred that curcumin-suppressed Rb cells proliferation might be via modulation of cell cycle, as CyclinD1 was down-regulated and p21 was up-regulated by addition of curcumin. Similar finding was reported by Yu et al [ 31 ] that curcumin induced G1 phase arrest via down-regulations of Cyclin D3, CDK2/6, and up-regulations of p21 and p27. CyclinD1 and p21 are two key molecules in cell-cycle progression.…”
Section: Discussionsupporting
confidence: 91%
“…Sreenivasan and his colleagues have reported that curcumin suppressed the expression of multidrug resistance associated protein 1 (MDR1) [ 29 ], thereby rendering Rb cells more sensitive to chemotherapy [ 30 ]. Another investigation demonstrated that curcumin induced the apoptosis of Y79 cells possibly through activating JNK and p38 MAPK pathways [ 31 ]. Although these authors have identified some anti-tumor activities of curcumin on Rb, additional studies are required to cross-check the anti-tumor properties of curcumin on other Rb cell types, and to decode the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…If applied alone, curcumin and AA were cytotoxic toward cell lines of different tumor types with curcumin exhibiting stronger cytotoxicity than AA. Our results are in line with other reports on the inhibitory activity of curcumin (Bimonte et al, 2016 ; Guzzarlamudi et al, 2016 ; Kasi et al, 2016 ; Ye et al, 2016 ; Yu et al, 2016 ; Zeng et al, 2016 ) and AA (Chen et al, 2015 ; Fukui et al, 2015 ; Jacobs et al, 2015 ; Sunil Kumar et al, 2015 ; Venturelli et al, 2015 ). The anticancer effects of curcumin in vitro and in vivo are primarily due to the activation of apoptotic pathways in cancer cells as well as the inhibition of mechanisms related to the tumor microenvironments such as inflammation, angiogenesis, invasion, and metastasis.…”
Section: Discussionsupporting
confidence: 93%
“…Yu et al found than the activation of c-Jun N-terminal kinase (JNK) and p38 MAPK on the retinoblastoma Y79 cell line was induced by curcumin. This finding was corroborated by the use of SP600125 and SB203580, specific inhibitors of JNK and p38 MAPK respectively, which inhibited the apoptosis of the retinoblastoma cell line and suppressed the activation of caspase-9 and -3 [34]. Li et al studied the effect of curcumin on SO-Rb50 and Y79 cells, retinoblastoma cell lines, and found out that curcumin inhibited cell proliferation, induced apoptosis and inhibited the migratory and invasive capacities of the retinoblastoma cell lines.…”
Section: Eye Antitumor Activity (Retinal and Choroidal Tumors)mentioning
confidence: 90%